Foliar biofertilizers in the agronomic performance, chemical composition, and in vitro degradability of megathyrsus maximus pasture - Arana Sánchez, Denisse (2024)
This research was conducted in the Livestock and Pasture Program of the Pichilingue Tropical Experimental Station of INIAP and in the Rumiology Laboratory at UTEQ. The study evaluated the application of foliar biofertilizers on the agronomic performance, chemical composition, and in vitro ruminal degradability of Saboya grass. The Tilley and Terry in vitro digestibility technique was employed, with four treatments and four replications. The results indicate that foliar biofertilization did not have significant effects (P>0.05) on the chemical composition, except for the acid detergent fiber (ADF) content. Foliar biofertilization also did not show clear and conclusive effects on the in vitro ruminal degradation of dry matter, as the evaluated variables were similar between treatments (P<0.05), while the degradation rate (kd) and effective degradability (ED) showed differences (P>0.05).